RCAN1 in cardiovascular diseases: molecular mechanisms and a potential therapeutic target - Shuai Wang; Yuqing Wang; Kaixin Qiu; Jin Zhu; Yili Wu (BMC, 2020)
Abstract Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide. Considerable efforts are needed to elucidate the underlying mechanisms for the prevention and treatment of CVDs. Regulator of calcineurin 1 (RCAN1) is involved in both development/maintenance of the cardiovascular system and the pathogenesis of CVDs. RCAN1 reduction protects against atherosclerosis by reducing the uptake of oxidized low-density lipoproteins, whereas RCAN1 has a protective effect on myocardial ischemia/reperfusion injury, myocardial hypertrophy and intramural hematoma/aortic rupture mainly mediated by maintaining mitochondrial function and inhibiting calcineurin and Rho kinase activity, respectively. In this review, the regulation and the function of RCAN1 are summarized. Moreover, the dysregulation of RCAN1 in CVDs is reviewed. In addition, the beneficial role of RCAN1 reduction in atherosclerosis and the protective role of RCAN1 in myocardial ischemia/reperfusion injury, myocardial hypertrophy and intramural hematoma /aortic rupture are discussed, as well as underlying mechanisms. Furthermore, the therapeutic potential and challenges of targeting RCAN1 for CVDs treatment are also discussed.